Actinomycosis of antrochoanal polyp: a rare entity - Pol, Shashikant A.; Dass, Arjun; Gupta, Nitin; Mahajan, Aditi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Antrochoanal polyp is a benign lesion, originating from the mucosa of the maxillary sinus, grow into maxillary sinus, nasal cavity and posteriorly to involve the choana. Nasal obstruction and nasal discharge are their main symptoms. Epistaxis is rare as seen in infected cases. Clinical assessment along with radiology helps in the diagnosis of antrochoanal polyp. We hereby describe a case of infected antrochoanal polyp in a 20-year-old female who presented with unilateral nasal obstruction, nasal discharge and intermittent epistaxis. Complete excision was done through endoscopic approach. On histopathology it showed secondary infection caused by actinomycosis which is extremely rare finding. This might be the first case report of actinomycosis infection in antrochoanal polyp as it was not found previously in any antrochoanal polyp case. Patient was followed till 6 month without any symptom.